A New Strategy for Obesity Treatment: Revealing the Frontiers of Anti-obesity Medications - Huang, Pan-feng; Wang, Qi-Yu; Chen, Rong-Bin; Wang, Ya-Di; Wang, Yuan-Yuan; Liu, Jiang-Hua; Xiao, Xin-Hua; Liao, Zhe-Zhen (Current Molecular Medicine, 2025)
Obesity dramatically increases the risk of type 2 diabetes, fatty liver, hypertension, cardiovascular disease, and cancer, causing both declines in quality of life and life expectancy, which is a serious worldwide epidemic. At present, more and more patients with obesity are choosing drug therapy. However, given the high failure rate, high cost, and long design and testing process for discovering and developing new anti-obesity drugs, drug repurposing could be an innovative method and opportunity to broaden and improve pharmacological tools in this context. Because different diseases share molecular pathways and targets in the cells, anti-obesity drugs discovered in other fields are a viable option for treating obesity. Recently, some drugs initially developed for other diseases, such as treating diabetes, tumors, depression, alcoholism, erectile dysfunction, and Parkinson's disease, have been found to exert potential anti-obesity effects, which provides another treatment prospect. In this review, we will discuss the potential benefits and barriers associated with these drugs being used as obesity medications by focusing on their mechanisms of action when treating obesity. This could be a viable strategy for treating obesity as a significant advance in human health.
Keywords: pharmacotherapy